2019
DOI: 10.24925/turjaf.v7i3.504-510.2318
|View full text |Cite
|
Sign up to set email alerts
|

Adaçayı (Salvia spp.) Türlerinde Çimlenme ve Çıkış Performansını Arttırıcı Uygulamalar

Abstract: In this study, Common Sage (Salvia officinalis L.) and Anatolian Sage (Salvia fruticosa Mill.) seeds, which are important medicinal plants, were used as plant material. The seeds of the Salvia genus have dormancy as they have seed husks containing a mucilaginous layer. For this reason, in order to improve the germination and emergence performance of seeds and to increase the quality of seeds, nine pre-sowing treatments (KNO3 application, GA3 application, polymer coating, polymer coating + KNO3, polymer coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Dormancy is an important factor in preventing germination (Finkelstein et al, 2008). In studies performed with different sage species, the germination strength value was 31% in S. fruticosa (Sonmez et al, 2019), 25.50% in S. pomifera (Ozcan et al, 2014), 76% in S. cyanescens, 29% (Yucel and Yılmaz 2009), in S. verticillata (Tursun 2020) and in 41% S. sclarea (Joshi and Pant, 2010) was recorded. While the germination value of M. vulgare was determined as 88% (Dadach et al, 2015), this value was very low 1.25% in M. parviflorum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Dormancy is an important factor in preventing germination (Finkelstein et al, 2008). In studies performed with different sage species, the germination strength value was 31% in S. fruticosa (Sonmez et al, 2019), 25.50% in S. pomifera (Ozcan et al, 2014), 76% in S. cyanescens, 29% (Yucel and Yılmaz 2009), in S. verticillata (Tursun 2020) and in 41% S. sclarea (Joshi and Pant, 2010) was recorded. While the germination value of M. vulgare was determined as 88% (Dadach et al, 2015), this value was very low 1.25% in M. parviflorum subsp.…”
Section: Discussionmentioning
confidence: 99%
“…However, aromatic medicinal plants are not yet grown in sufficient quantities to meet demand. Therefore, increasing the amount of medicinal aromatic plants in the existing cultivated areas should become a priority issue (Sonmez et al, 2019). Kordali et al, (2005) identified the components of the essential oil of the tarragon plant and found thirty components that account for 99.5% of the essential oil content.…”
Section: Introductionmentioning
confidence: 99%